Oral Cavity Calprotectin and Lactoferrin Levels in Relation to Radiotherapy - Keskin Mutlu; Kompuinen Jenna; Harmankaya İlknur; Karaçetin Didem; Nissilä Verneri; Gürsoy Mervi; Sorsa Timo; Gürsoy Ulvi Kahraman (Switzerland, 2022)
Background: Lactoferrin, an iron-binding glycoprotein, and calprotectin, a calcium binding protein, are sensitive markers of inflammation and their fecal levels increase during radiotherapy of prostate cancer patients. With this background, we analyzed mouthrinse calprotectin and lactoferrin levels of head- and neck-cancer patients before, during and after radiotherapy.
Methods: Twenty cancer patients (mean age 55.85 ± 15.01, 80% male), who had been planned to undergo radiotherapy to the head and neck area, were included in this study. Mouthrinse samples were collected before radiotherapy, at the 3rd and 6th weeks of radiotherapy and 4 weeks after the radiotherapy. Mouthrinse samples were analyzed for calprotectin and lactoferrin using commercial ELISA kits.
Results: Calprotectin levels increased significantly during radiotherapy (p = 0.022). Both markers, lactoferrin (p = 0.011) and calprotectin (p = 0.006), decreased significantly after the treatment.
Conclusions: Present study results may suggest that the elevations in calprotectin and lactoferrin levels during radiotherapy reflect the increased and emerging inflammatory environment in the oral cavity, thus may increase the risk of periodontal disease initiation or progression.